2022
DOI: 10.3390/cancers14225610
|View full text |Cite
|
Sign up to set email alerts
|

CD155 Cooperates with PD-1/PD-L1 to Promote Proliferation of Esophageal Squamous Cancer Cells via PI3K/Akt and MAPK Signaling Pathways

Abstract: Background: Esophageal cancer is still a leading cause of death among all tumors in males, with unsatisfactory responses to novel immunotherapies such as anti-PD-1 agents. Herein, we explored the role of CD155 in esophageal squamous cell cancer (ESCA) and its underlying molecular mechanisms. Methods: Publicly available datasets were used for differential gene expression and immune infiltration analyses, and their correlation with patient survival. A total of 322 ESCA and 161 paracancer samples were collected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…VTCN1 (also known as B7-H4) and PVR (also known as CD155) are 2 other immune checkpoint genes. Numerous studies evaluated the effect of VTCN1 and PVR in esophageal squamous cancer and found that VTCN1 and PVR expression is associated with tumor progression and promotes cell proliferation [ 70 73 ]. However, the value of these 2 genes in EAC has not been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…VTCN1 (also known as B7-H4) and PVR (also known as CD155) are 2 other immune checkpoint genes. Numerous studies evaluated the effect of VTCN1 and PVR in esophageal squamous cancer and found that VTCN1 and PVR expression is associated with tumor progression and promotes cell proliferation [ 70 73 ]. However, the value of these 2 genes in EAC has not been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Histochemistry score was used for semi-quantitative analysis of the CXCL12 protein expression level, and it was evaluated using the following formula: CXCL12-score = the staining intensity × the rate of positive cells ( 26 , 27 ). The intensity of positive cells was graded as 0 (negative, unstained), 1 (weak), 2 (moderate), and 3 (strong).…”
Section: Methodsmentioning
confidence: 99%